Why mindfulness matters in musculoskeletal therapies: a narrative review - Bablis, Peter; Day, Ryan R.; Bablis, Sophia; Pollard, Henry (Frontiers in Psychology, 2025)
This narrative review explores the integration of mindfulness-based interventions (MBIs) into musculoskeletal (MSK) care, based on the premise that addressing the mind–body interface can enhance patient outcomes. First, we outline how chronic stress affects twelve physiological systems and contributes to the onset and persistence of MSK conditions. Second, we synthesise evidence showing that MBIs mitigate these stress effects through mechanisms such as improved attention regulation, interoceptive awareness, and reduced catastrophising. Third, we highlight Neuro-Emotional Technique (NET) as a practitioner-facilitated hybrid-MBI exemplar that targets unresolved emotional stress patterns and aligns with the biopsychosocial model of healthcare. We also note contraindications via red and yellow flag considerations, emphasising the importance of careful patient selection and responsible application. Taken together, this review provides a rationale for incorporating MBIs as adjuncts to conventional therapies, supporting recovery, fostering resilience, and advancing patient-centred MSK care.